Briquette Production: An Alternative for Organic Waste Management in Arjasari Village, Arjasari District - Hakim, Haikal Farhannul; Putri, Amelia; Az-zachra, Nasywa Dewant; Anggoro, Bimo Tri; Nurmala, Riri Riyani; Fajriah, Alisa Noor; Reyhan, Shakila; Susanti, Dian (Jurnal Pengabdian Tri Bhakti, 2025)
Arjasari Village is one of the villages located in Arjasari Subdistrict, Bandung Regency, with an area of approximately 768 hectares, where the majority of the population works in agriculture. The abundance of agricultural products and the large amount of organic waste produced provide Arjasari Village with an opportunity to develop alternative energy innovations in the form of briquette production. Until now, most organic waste has not been optimally utilized, even though it can be processed into a renewable energy source. Some people still rely on firewood or torches for cooking, so briquettes are seen as a strategic solution to reduce dependence on firewood, LPG, and kerosene, which are increasingly limited and non-renewable. The KKNM (Student Community Service Program) in Arjasari Village for processing organic waste into briquettes is expected to provide tangible benefits to the community, such as: (1) increasing the utilization of village organic waste into useful products; (2) meeting the need for alternative energy independently and sustainably; (3) opening up business opportunities and improving the community's economy. Thus, briquettes made from organic waste can be one of the environmentally friendly and sustainable alternative energy solutions in Arjasari Village